Regional elections of 2020 in the Irkutsk region: progress, results, and organization - Zulyar, Yuriy (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
The regular conduct of elections and the compliance of their procedure with the current legislation is a prerequisite for the functioning of a democratic political system. The occurrence of emergencies, such as military operations, pandemics, and the like, is a serious problem and challenge for the country’s leadership. The resulting social tension and instability, changes in the current electoral order and electoral procedures, pose a threat to the ruling regime and provide additional opportunities for the opposition. The article shows the activities of the leadership of Russia and the Irkutsk region in the context of a Covid pandemic during the regional elections of 2020. The legislation was changed and special measures were organized to ensure compliance with all epidemiological norms and to prevent a significant increase in the number of cases. A special feature of the elections in the Irkutsk region was the holding of early, really competitive elections for the governor, in which a Kremlin protege and a local representative of the Communist Party fought. In a really difficult situation, the elections were held calmly and without any special violations of the law and moral norms. Despite the fundamental nature of the struggle for the governor’s seat, the voter turnout was low and fundamentally lower than the plebiscite held in July of the same year to amend the Constitution of the Russian Federation.

Regularne przeprowadzanie wyborów i zgodność ich procedury z obowiązującym ustawodawstwem jest warunkiem funkcjonowania demokratycznego systemu politycznego. Występowanie sytuacji nadzwyczajnych, takich jak operacje wojskowe, pandemie i tym podobne, stanowi poważny problem i wyzwanie dla kierownictwa państwa. Wynikające z tego napięcia społeczne i niestabilność, zmiany w dotychczasowym porządku i procedurach wyborczych, stanowią zagrożenie dla rządzącego reżimu i stwarzają dodatkowe możliwości dla opozycji. W artykule przedstawiono działania kierownictwa Rosji i obwodu irkuckiego w kontekście pandemii Covid podczas wyborów regionalnych w 2020 roku. Zmieniono ustawodawstwo i zorganizowano specjalne środki, aby zapewnić przestrzeganie wszystkich norm epidemiologicznych i zapobiec znacznemu wzrostowi liczby zachorowań. Szczególną cechą wyborów w obwodzie irkuckim było przeprowadzenie przedterminowych, naprawdę konkurencyjnych wyborów gubernatora, w których walczyli protegowany Kremla i lokalny przedstawiciel partii komunistycznej. W naprawdę trudnej sytuacji wybory odbyły się spokojnie, bez szczególnych naruszeń prawa i norm moralnych. Mimo fundamentalnego charakteru walki o fotel gubernatora, frekwencja wyborcza była niska i zasadniczo niższa od przeprowadzonego w lipcu tego samego roku plebiscytu w sprawie zmiany Konstytucji Federacji Rosyjskiej.
Wybory roku 2020 w obwodzie irkuckim: przebieg, wyniki i organizacja
Keywords: regional elections in Russia; Irkutsk region; eatures of elections in the context of a pandemic; early elections of the governor; wybory regionalne w Rosji; obwód irkucki; cechy wyborów w kontekście pandemii; przedterminowe wybory gubernatora